2018
DOI: 10.1039/c8cc05271a
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-based tools for the investigation of cellular environments

Abstract: Biological probes constructed from lanthanides can provide a variety of readout signals, such as the luminescence of Eu(iii), Tb(iii), Yb(iii), Sm(iii) and Dy(iii), and the proton relaxation enhancement of Gd(iii) and Eu(ii). For numerous applications the intracellular delivery of the lanthanide probe is essential. Here, we review the methods for the intracellular delivery of non-targeted complexes (i.e. where the overall complex structure enhances cellular uptake), as well as complexes attached to a targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 153 publications
(228 reference statements)
1
73
0
Order By: Relevance
“…Recent years have seen efforts to engineer lanthanide complexes for cell-based, TGL biosensing and imaging applications including sensing of pH, metal ions, nucleic acids, enzymatic activities, and PPIs ( Aulsebrook et al., 2018 ; Mathieu et al., 2018 ; New et al., 2010 ; Rajendran et al., 2014 ; Zhang et al., 2018 ). A number of studies reported proof-of-concept LRET microscopic imaging of molecular interactions between Tb(III)- or Eu(III)-labeled and fluorophore-labeled species on cell surfaces including G-protein-coupled receptor (GPCR) ligand binding ( Delbianco et al., 2014 ), GPCR oligomerization ( Comps-Agrar et al., 2012 ; Faklaris et al., 2015 ), cadherin interactions ( Linden et al., 2015 ), and interactions between complementary morpholino probes in zebrafish embryos ( Cho et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent years have seen efforts to engineer lanthanide complexes for cell-based, TGL biosensing and imaging applications including sensing of pH, metal ions, nucleic acids, enzymatic activities, and PPIs ( Aulsebrook et al., 2018 ; Mathieu et al., 2018 ; New et al., 2010 ; Rajendran et al., 2014 ; Zhang et al., 2018 ). A number of studies reported proof-of-concept LRET microscopic imaging of molecular interactions between Tb(III)- or Eu(III)-labeled and fluorophore-labeled species on cell surfaces including G-protein-coupled receptor (GPCR) ligand binding ( Delbianco et al., 2014 ), GPCR oligomerization ( Comps-Agrar et al., 2012 ; Faklaris et al., 2015 ), cadherin interactions ( Linden et al., 2015 ), and interactions between complementary morpholino probes in zebrafish embryos ( Cho et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The creation of Ln(III)based anion receptors is driven by the need for new sensing and imaging tools for biological, clinical and drug discovery research. [1][2][3] For example, an emissive Ln(III) receptor capable of binding bicarbonate (HCO 3 À ) selectively could be used to image spatial-temporal HCO 3 À dynamics in living cells using uorescence microscopy, 4 potentially aiding the diagnosis and treatment of diseases such as renal disease and glaucoma. 5 A Ln(III) receptor that binds adenosine diphosphate (ADP) selectively could allow real-time analysis of kinase enzyme activity by monitoring the production of ADP, 6 thereby providing a convenient luminescence assay for high throughput screening of potential kinase inhibitors for the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination of the luminescent lanthanide ion inside supramolecular chelates or cryptates can enhance the absorption by more than 1000-fold via the antenna effect and efficiently protect the lanthanide ion from the environment to circumvent PL quenching and yield high PL quantum yields [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Such bright and stable lanthanide complexes have been used in many different applications concerning highly sensitive, multiplexed, and background-free biological and chemical sensing and imaging [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%